Efficacy and safety of first-line lorlatinib versus crizotinib in patients with advanced, ALK-positive non-small-cell lung cancer: updated analysis of data from the phase 3, randomised, open-label CROWN study. Issue 4 (April 2023) - Solomon, Benjamin J; Bauer, Todd M; Mok, Tony S K; Liu, Geoffrey; Mazieres, Julien; de Marinis, Filippo; Goto, Yasushi; Kim, Dong-Wan; Wu, Yi-Long; Jassem, Jacek; López, Froylán López; Soo, Ross A; et al.
Summary: Background: After a median follow-up of 18·3 months, the third-generation anaplastic lymphoma kinase (ALK) tyrosine-kinase inhibitor, lorlatinib, improved progression-free survival in patients with treatment-naive, ALK -positive non-small-cell lung cancer in the phase 3 CROWN study. Here we report updated efficacy data, including intracranial activity, from an unplanned analysis after 3 years of follow-up. Methods: CROWN is an ongoing, international, randomised, open-label phase 3 trial done in 104 centres in 23 countries worldwide. Eligible participants were aged 18 years and older or aged 20 years and older (depending on local regulations) with advanced, ALK -positive non-small-cell lung cancer, had received no previous systemic treatment for metastatic disease, had at least one extracranial measurable target lesion (according to the Response Evaluation Criteria in Solid Tumours [RECIST], version 1.1), and had an Eastern Cooperative Oncology Group performance status score of 0–2. Patients were randomly assigned (1:1) to oral lorlatinib 100 mg daily or oral crizotinib 250 mg twice daily in 28-day cycles. Randomisation was stratified by the presence or absence of brain metastasis, and by ethnicity. Since the primary endpoint of the study had been met at the planned interim analysis, no further formal analysis of progression-free survival was planned, per protocol. The current unplanned analysis was done to further characterise tumour-related endpoints with a longer follow-up and is presented descriptively. For the planned study, the primary endpoint was progression-free survival assessed by blinded independent central review. Secondary endpoints included progression-free survival (investigator), objective response rate, intracranial objective response rate, time to intracranial progression, duration of response, intracranial duration of response, and safety. Efficacy endpoints were also assessed by the presence or absence of baseline brain metastases. This study is registered with ClinicalTrials.gov, NCT03052608 . Findings: Between May 11, 2017, and Feb 28, 2019, 425 patients were screened for eligibility, of whom 296 were enrolled and randomly assigned to the lorlatinib (n=149) or crizotinib (n=147) group. At data cutoff for this unplanned analysis (Sept 20, 2021), median duration of follow-up for progression-free survival was 36·7 months (IQR 31·3–41·9) for lorlatinib and 29·3 months (10·8–35·0) for crizotinib. Median progression-free survival by blinded independent central review was not reached (95% CI not reached–not reached) for lorlatinib and was 9·3 months (7·6–11·1) for crizotinib (hazard ratio [HR] 0·27 [95% CI 0·18–0·39]). 3-year progression-free survival was 64% (95% CI 55–71) in the lorlatinib group and 19% (12–27) in the crizotinib group. Progression-free survival (investigator), objective response rate, intracranial objective response rate, time to intracranial progression, and duration of response were improved with lorlatinib versus crizotinib. In patients with baseline brain metastases (n=37 lorlatinib; n=39 crizotinib), the HR for time to intracranial progression for lorlatinib versus crizotinib was 0·10 (95% CI 0·04–0·27); in patients without baseline brain metastases (n=112 lorlatinib; n=108 crizotinib), the HR was 0·02 (95% CI 0·002–0·14). In patients without brain metastases, one (1%) in the lorlatinib group and 25 (23%) in the crizotinib group had intracranial progression. Grade 3–4 adverse events occurred in 113 (76%) of 149 patients (most commonly due to altered lipid levels) with lorlatinib and in 81 (57%) of 142 patients with crizotinib. Adverse events led to treatment discontinuation in 11 (7%) patients in the lorlatinib group and 14 (10%) patients in the crizotinib group. There were no new safety signals. Interpretation: These updated, long-term data from CROWN show the durable benefit of lorlatinib over crizotinib in patients with treatment-naive, ALK -positive non-small-cell lung cancer and support the use of first-line lorlatinib in patients with and without baseline brain metastases. Funding: Pfizer.